Characterization of cholinesterases in Chironomus riparius and the effects of three herbicides on chlorpyrifos toxicity - Pérez, Joanne
In this study, the toxicities of four pesticides (the herbicides atrazine, terbuthylazine, metolachlor and the insecticide chlorpyrifos) previously detected in the Alqueva reservoir/dam (south of Portugal) were evaluated individually and in binary combinations of the herbicides and the insecticide using fourth-instar larvae of the aquatic midge Chironomus riparius.Chlorpyrifos induced toxicity to midges in all the 48h toxicity bioassays performed. The swimming behaviour of the larvae was impaired, with EC50values ranging from 0.15 to 0.17μg/L. However, neither s-triazine (atrazine and terbuthylazine) herbicides nor metolachlor alone at concentrations up to 200μg/L caused significant toxicity to C. riparius. When combined with both s-triazine herbicides, chlorpyrifos toxicity was enhanced by approximately 2-fold when tested in a binary mixture experimental setup, at the 50% effective concentration levels.To evaluate how chlorpyrifos toxicity was being increased, the cholinesterases (ChE) were characterized biochemically using different substrates and selective inhibitors. The results obtained suggested that the main enzyme present in this species is acetylcholinesterase (AChE) and therefore it was assayed upon C. riparius exposures to all pesticides individually and as binary mixtures. Although atrazine and terbuthylazine are not effective inhibitors of AChE, the potentiation of chlorpyrifos toxicity by the two s-triazine herbicides was associated with a potentiation in the inhibition of AChE in midges; both s-triazine herbicides at 200. μg/L increased the inhibition of the AChE activity by 7 and 8-fold, respectively. A strong correlation was observed between swimming behaviour disturbances of larvae and the inhibition of the AChE activity. In contrast, metolachlor did not affect chlorpyrifos toxicity at any of the concentrations tested. Therefore, the herbicides atrazine and terbuthylazine can act as synergists in the presence of chlorpyrifos, increasing the toxicity and consequently underestimating risk based on single chemical levels.